Hubungan Antara Kecerdasan Adversitas Dengan Prestasi Akademik Pada Aktivis Organisasi Kemahasiswaan Fakultas Psikologi Universitas Muhammadiyah Surakarta - AQILA, FIKRI YUMNA (2016)
THE CORRELATION BETWEEN THE ADVERSITY QUOTIENT AND THE ACADEMIC ACHIEVEMENT IN THE ACTIVISTS OF STUDENT ORGANIZATIONS OF PSYCHOLOGY FACULTY, MUHAMMADIYAH UNIVERSITY OF SURAKARTA Fikri Yumna Aqila Psychology Faculty, Muhammadiyah University of Surakarta ABSTRACT Activists of university student organizations are not easy to have a good academic achievement. It is proved by the presence of university students who have a low grade point average because of not being able to learn the lecturing materials well. Therefore, the activists are hoped to have a high adversity quotient in order to be able to stand the difficulties that must be faced in the academic or non academic aspects, therefore, it supports the attainment of a good academic achievement. The objectives of this research were to know the correlation between the adversity quotient and the academic achievement, the effective contribution of the adversity quotient on the academic achievement, the level of the adversity quotient and the level of the academic achievement. Hypothesis proposed was that there was a positive correlation between the adversity quotient and the academic achievement in the activists of university student organizations. The method in this research used the quantitative method. The amount of the research subjects was 80 university students who became the organizers and members of university student organizations who were minimally in the 3rd semester. The methods of data collection used the scale of adversity quotient and the documentation of the Grade Point Average (GPA). Meanwhile, the method of sampling used in this research was the kind of incidental sampling. From the result of the normality test on the variable of the academic achievement obtained Kolmogorov-Smirnov Z = 0.563, with significance = 0.909 (p > 0.05). Based on the linear test, it was obtained F score in the Deviation from Linierity = 1.150 and significance (p) = 0.339; (p > 0.05). Based on the results of calculation using product moment, it was obtained the score of the coefficient of correlation (rxy) as much as 0.473; significance (p) = 0.000 (p < 0.01), that meant that there was a positively significant correlation between the adversity quotient and the academic achievement in the activists of university student organizations. The effective contribution of the variable of the adversity quotient on the academic achievement in the activists of university student organizations was as much as 22.4%. From the results of this research, it was also known that the adversity quotient and the academic achievement in the activists of university student organizations were categorized as high. Keywords: Adversity Quotient, Academic Achievement